Proceedings of the 59th Annual Meeting of the Association for Computational Linguistics and the 11th International Joint Confer 2021
DOI: 10.18653/v1/2021.acl-demo.18
|View full text |Cite
|
Sign up to set email alerts
|

SummVis: Interactive Visual Analysis of Models, Data, and Evaluation for Text Summarization

Abstract: Novel neural architectures, training strategies, and the availability of large-scale corpora haven been the driving force behind recent progress in abstractive text summarization. However, due to the black-box nature of neural models, uninformative evaluation metrics, and scarce tooling for model and data analysis, the true performance and failure modes of summarization models remain largely unknown. To address this limitation, we introduce SUMMVIS, an open-source tool for visualizing abstractive summaries tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…If a model can pinpoint which portion of a summary is inconsistent, some work has shown that corrector models can effectively re-write the problematic portions and often remove the inconsistency . Furthermore, fine-grained consistency scores can be incorporated into visual analysis tools for summarization such as Summ-Viz (Vig et al, 2021). The SUMMAC ZS model is directly interpretable, whereas the SUMMAC CONV is slightly more opaque, due to the inability to trace back a low score to a single sentence in the document being invalidated.…”
Section: Choice Of Granularitymentioning
confidence: 99%
“…If a model can pinpoint which portion of a summary is inconsistent, some work has shown that corrector models can effectively re-write the problematic portions and often remove the inconsistency . Furthermore, fine-grained consistency scores can be incorporated into visual analysis tools for summarization such as Summ-Viz (Vig et al, 2021). The SUMMAC ZS model is directly interpretable, whereas the SUMMAC CONV is slightly more opaque, due to the inability to trace back a low score to a single sentence in the document being invalidated.…”
Section: Choice Of Granularitymentioning
confidence: 99%
“…However, there is a need to address issues such as a proper model and data analysis tool and understanding the failure model of summarization. SummVis [22], an open-source tool, allows us to visualize, generate a summary, and analyze the summarization models and the evaluation metrics used. Topic modeling has been recently used in text summarization to identify hidden topics in the document [23].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Section 2, we found several mentioned human evaluation is challenging since annotators need to read long source documents. Some prior work has suggested highlighting spans in the source document that align with the summary (Hardy et al, 2019;Kryscinski et al, 2020;Vig et al, 2021) as shown in Figure 1. However, these efforts have exclusively focused on news summarization with relatively short source documents, like CNN/DM (804 words) (Nallapati et al, 2016) or XSUM (438 words) (Narayan et al, 2018).…”
Section: S|mentioning
confidence: 99%